Arabidopsis TH2 Encodes the Orphan Enzyme Thiamin Monophosphate Phosphatase. Issue 10 (27th September 2016) - Mimura, Manaki; Zallot, Rémi; Niehaus, Thomas D.; Hasnain, Ghulam; Gidda, Satinder K.; Nguyen, Thuy N.D.; Anderson, Erin M.; Mullen, Robert T.; Brown, Greg; Yakunin, Alexander F.; de Crécy-Lagard, Valérie; Gregory, Jesse F.; et al.
Abstract : Genomic, transcriptomic, genetic, and biochemical evidence implicates Arabidopsis TH2 in dephosphorylation of thiamin monophosphate, a key step in biosynthesis of thiamin diphosphate, an essential cofactor for central metabolic enzymes. Abstract: To synthesize the cofactor thiamin diphosphate (ThDP ), plants must first hydrolyze thiamin monophosphate (ThMP ) to thiamin, but dedicated enzymes for this hydrolysis step were unknown and widely doubted to exist. The classical thiamin-requiring th2-1 mutation in Arabidopsis thaliana was shown to reduce ThDP levels by half and to increase ThMP levels 5-fold, implying that the THIAMIN REQUIRING2 ( TH2 ) gene product could be a dedicated ThMP phosphatase. Genomic and transcriptomic data indicated that TH2 corresponds to At5g32470, encoding a HAD (haloacid dehalogenase) family phosphatase fused to a TenA (thiamin salvage) family protein. Like the th2-1 mutant, an insertional mutant of At5g32470 accumulated ThMP, and the thiamin requirement of the th2-1 mutant was complemented by wild-type At5g32470 . Complementation tests in Escherichia coli and enzyme assays with recombinant proteins confirmed that At5g32470 and its maize ( Zea mays ) orthologs GRMZM2G148896 and GRMZM2G078283 are ThMP -selective phosphatases whose activity resides in the HAD domain and that the At5g32470 TenA domain has the expected thiamin salvage activity. In vitro and in vivo experiments showed that alternative translation start sites direct the At5g32470 protein to the cytosol and potentially also to mitochondria. Our findings establish that plants have a dedicated ThMP phosphatase and indicate that modest (50%) ThDP depletion can produce severe deficiency symptoms.